Fatigue fracture of the second rib in a professional athlete - Zdziebło, Katarzyna; Łapińska, Urszula; Machała-Ćwikła, Ewelina; Zdzieblo, Piotr; Ćwikła, Piotr; Zdziebło, Anna; Bieniasz, Anna; Machała, Dominika; Machała, Kamila (Quality in Sport, 2024)
A fatigue fracture, also known as stress fracture or overuse fracture, is caused by the summation of micro-injuries resulting from a chronic state of bone overload. It affects 1.4 %- 4.4 % of professional athletes. The most common site of fatigue fractures are the lower limbs. This is related to the heavy load caused by body weight and performing dynamic activities like jumping, running. Typical fractures are fractures of the fifth metatarsal bone, fibula and tibia, and less common fractures of the femur. Fractures involving the bones of the upper limbs and thorax are less commonly reported in the literature. It affect athletes in strength sports and athletes who perform dynamic and repetitive movements with their upper limbs, most often boxers, weightlifters, wrestlers, judokas, swimmers, golfers, rowers. Fractures in the thorax most often involve the first rib. Fractures of ribs II through XII are extremely rarely described. We present an unusual case of a second rib fracture in a professional athlete. A 26-year-old athlete training in racewalking reported increasing pain in the left scapula area 7 days before competing in the European Championships. Immediately after the competition, the pain changed location to the anterior thorax area, making movement of the upper limb and breathing much more difficult. A chest tomography was performed and it revealed a fatigue fracture of the second rib on the left side. The case report presents an atypical fracture in a female racewalking athlete and presents the uncharacteristic symptoms accompanying this fracture. Incorrect initial diagnosis and application of physiotherapy procedures without performing basic diagnostic tests, delay the diagnosis and initiation of proper treatment, and thus the athlete’s recovery.